Exploring factors contributing to falls in home-dwelling older adults: A cross-sectional study in Northeastern Thailand - Boonkhao, Laksanee; Choochouy, Nattagorn; Rattanachaikunsopon, Pongsak; Laosupap, Kitti; Saenrueang, Thitima; Labcom, Chiraporn; Chakhamrun, Nittaya; Boonsang , Arun; Butsorn, Aree (Narra Sains Indonesia, 2025)
Falls are the most common accidents among older adults in home settings. Older adults experience falls due to several risk factors. In 2005, Thailand became an aging society, with projections indicating that by 2021, older adults would represent the majority of the population, and by 2035, approximately 30 percent of the population would be older adults. Approximately 3 million fall episodes transpire among older adults each year in Thailand, leading to almost 60,000 hospitalizations. The aim of this study was to examine the factors associated with falls among older adults in northeastern Thailand, hypothesizing that characteristics such as cognitive capacity, visual acuity, hearing acuity, balance ability, and mobility are associated with fall risk in this population. A cross-sectional analytical study involved 264 older adults aged 60 years or older using a questionnaire and a battery of tests that assessed the participants’ cognitive capacity, eyesight proficiency, hearing ability, balancing ability, and mobility. The variables that exhibited a statistically significant association (p<0.05) were employed in a binary logistic regression analysis. The results revealed that falls among home-living older adults were significantly associated with sex, family size, congenital issues, and mobility. Older adults who were female and had a large family, congenital disorders, or mobility impairments were at a higher risk of falls, which emphasizes the need for personalized prevention strategies. It is recommended to adopt a proactive healthcare strategy to prevent falls and ensure safe living conditions. Interventions aimed at improving balance, mobility, and mental health, as well as encouraging an active lifestyle, may reduce the risk of falls among older adults living in the community. The findings may aid private and government agencies in developing effective fall prevention programs for older adults living at home.